Common Fixed Points of Intuitionistic Fuzzy Maps for Meir-Keeler Type Contractions. (21st October 2018) - Kanwal, Shazia; Azam, Akbar
Abstract : The main purpose of this paper is to establish and prove some new common fixed point theorems for intuitionistic fuzzy maps in the context of ( α, β ) -cut sets of intuitionistic fuzzy sets on a complete metric space in association with the Hausdorff metric. Furthermore, the technique of Meir-Keeler (shortly, M-K) contraction is applied to obtain common fixed point of intuitionistic fuzzy compatible maps and fixed points of Kannan type intuitionistic fuzzy set-valued contractive mappings. Our results generalize M-K type fixed point theorem along with its various generalizations. Some nontrivial examples have been furnished in the support of the main results.